2018
DOI: 10.22159/ajpcr.2018.v11i8.26359
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Nanoemulsion as a Carrier for Topical Delivery System by Box-Behnken Design

Abstract: Objective: The aim of this study was to develop a nanoemulsion for topical delivery. Methods: Topical nanoemulsion was prepared by homogenization method. Box-behnken design was utilized to study the effect of oil, surfactant and Co-surfactant, on droplet size, entrapment efficiency and drug release. Nabumetone a non-steroidal anti-inflammatory drug was incorporated in castor oil with Tween 80 and Polyethylene glycol 600 to form the nanoemulsion by homogenization method. The nanoemulsion was further subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 7 publications
(7 reference statements)
2
18
0
Order By: Relevance
“…Some recently approved commercial topical formulations of 5-FU (0.5%) include Carac ® ; Sanofi, Gentilly, France [ 20 ], Fluoroplex 1% 5-FU solution (Allergan, Inc., Irvine, CA, USA), creams (Efudex ® , Valeant Pharmaceuticals, Bridgewater, NJ, USA) and a 0.5% microsphere-based cream (Carac ® , Valeant Pharmaceuticals) [ 21 ]. A report has suggested that commercially available topical products offer the demerit of low retention time at the delivery site that results in inadequate skin permeation along with skin irritation reactions, such as dryness, redness, swelling, and burning pain of the upper layer of skin [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some recently approved commercial topical formulations of 5-FU (0.5%) include Carac ® ; Sanofi, Gentilly, France [ 20 ], Fluoroplex 1% 5-FU solution (Allergan, Inc., Irvine, CA, USA), creams (Efudex ® , Valeant Pharmaceuticals, Bridgewater, NJ, USA) and a 0.5% microsphere-based cream (Carac ® , Valeant Pharmaceuticals) [ 21 ]. A report has suggested that commercially available topical products offer the demerit of low retention time at the delivery site that results in inadequate skin permeation along with skin irritation reactions, such as dryness, redness, swelling, and burning pain of the upper layer of skin [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…To determine the pH of the gel formulation, 1 g of gel was dissolved in 25 mL of distilled water, followed by a pH measurement using a pH meter (Accumet meter 21039, Denver Instruments, USA) at 25 ± 1 • C. For instrument calibration, buffer solutions with known pH (3, 7, and 9) were employed. At room temperature, rheological characteristics of gel formulations were evaluated using a Brookfield viscometer (RVTD, USA) fitted with a UL-adapter [30]. With a #64 spindle, measurements were taken at a constant (40 rpm) as well as variable (10-120 rpm) shear speeds.…”
Section: Physico-chemical and Rheological Characterization Of Methotrexate Nanoemulsion Gelmentioning
confidence: 99%
“…Nanoemulsions [1] are high solubilizing and drug protection features have the potential to deliver proteins as well as other new (or traditional) active drug compounds. Although authors have suggested using nanoemulsion formulations for inflammation [2][3][4][5][6][7]. Budesonide (16,17-butylidenebis(oxy)-11,21-dihydroxypregna-1,4diene-3,20-dione) is a synthetic glucocorticoid steroid used in the treatment of asthma and an inflammatory bowel disease [9].…”
Section: Research Articlementioning
confidence: 99%